Metacognitive Model in Teaching Reading and Writing - Supeno Supeno (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2021)
The aims of this research is to know how teaching reading and writing are observed by metacognitive model and advantages and disadvantages in teaching process itself. The samples are 42 students of SMK An-Nurmaniyah Binong Permai and 39 students of SMK Yuppentek Tangerang The research is conducted in a qualitative research as the methodology. The research findings shows that most metacognitive processess are well-applied and their advantages and disadvantages in teaching reading and writing.